Association of preoperative fasting blood glucose with 1-year Harris Hip Score after hip fracture in older adults: a multicenter retrospective cohort study - Huazhong Liu; Jiajun Liao; Ji Li; Guixin Zhang; He Tian; Huai Wu; Haoze Yang; Shiwei Yang; Yun Lu (Frontiers in Endocrinology, 2026)
Background The impact of preoperative fasting blood glucose (FBG) on functional recovery after hip fracture remains uncertain. Methods We conducted a multicenter retrospective cohort study of older adults undergoing hip fracture surgery at three hospitals in Shenzhen, China, between January 2021 and May 2023. De-identified electronic health record data were pooled across centers. The primary outcome was 1-year functional recovery, assessed using the Harris Hip Score (HHS) and categorized as satisfactory (HHS ≥70) or unsatisfactory (HHS <70). Associations between FBG and recovery were evaluated using logistic regression in unadjusted, demographic-adjusted, and fully adjusted models including 28 prespecified clinical and perioperative covariates. Sensitivity analysis additionally adjusted for study center. FBG was analyzed continuously and categorically using World Health Organization cutoffs and tertiles. Generalized additive models assessed dose–response patterns, and subgroup analyses explored effect modification. Results Among 615 patients, higher preoperative FBG was associated with poorer 1-year functional recovery. In the fully adjusted model, each 1 mmol/L increase in FBG was associated with a 12% reduction in the odds of achieving HHS ≥70 (OR, 0.88; 95% CI, 0.80–0.96; P = 0.0036). Compared with FBG <6.1 mmol/L, FBG ≥7.0 mmol/L was associated with lower odds of satisfactory recovery (OR, 0.60; 95% CI, 0.37–0.98; P = 0.0414). Tertile analyses were consistent (highest vs lowest tertile: OR, 0.58; 95% CI, 0.34–1.00; P = 0.0485), with a significant linear trend. After additional adjustment for study center, the continuous association remained significant (OR, 0.89; 95% CI, 0.81–0.97; P = 0.0111), whereas categorical associations were attenuated. Smoothing curves suggested an approximately linear relationship. Subgroup findings were generally consistent but should be considered exploratory because no correction for multiple comparisons was applied. Conclusions Elevated preoperative FBG was independently associated with worse 1-year functional recovery after hip fracture surgery, particularly when modeled continuously. FBG may aid risk stratification and perioperative planning, but threshold-based findings require further validation. Prospective studies should determine whether perioperative glycemic management improves functional outcomes.